Hypolipidemic Activity of the Polysaccharide L-rhamnopyranosyl-6-O-methyl-galacturonan in Combined Administration with HMG-CoA Reductase and Cholesterol Absorption Inhibitors - E. E. Buyko; V. V. Ivanov; O. A. Kaidash; O. Yu. Rybalkina; E. A. Kiseleva; S. V. Krivoshchekov; T. L. Kiseleva; A. M. Guriev; M. V. Belousov (Разработка и регистрация лекарственных средств)
Introduction. Dyslipidemia treatment in many cases requires carefully selected combination of lipid-lowering drugs including bile acid sequestrants. A promising compound is L-rhamnopyranosyl-6-O-methyl-galacturonan (L-RAG), a polysaccharide obtained from the birch leaves (Betula pendula L.).Aim. To evaluate the lipid-lowering activity of L-RAG administered in combination with the HMG-CoA reductase inhibitor rosuvastatin or the cholesterol absorption inhibitor ezetimibe.Materials and methods. Hyperlipidemia in hamsters was reproduced by synthetic diet supplemented with 0.3 % cholesterol and 11 % coconut oil (HFCD). At the end of the experiment the levels of triacylglycerols (TAG), bile acids, total cholesterol (TC), cholesterol of low-density lipoproteins (LDL-C) and high-density lipoproteins (HDL-C) were determined in the blood serum using Chronolab Systems S. L. enzymatic kits (Spain), and atherogenic index (AI) was calculated.Results and discussion. L-RAG demonstrates a lipid-lowering effect in a model of diet-induced hyperlipidemia in hamsters. The decrease in the TC level was mainly caused by a decrease in the content of cholesterol in the atherogenic LDL fraction, which led to a decrease in AI. The use of rosuvastatin and ezetimibe in combination with L-RAG leads to a better lipid-lowering effect. The additive effect of the polysaccharide is mainly due to a decrease in the level of bile acids in the blood serum, which indicates its ability to absorb them in the intestinal lumen and interrupt enterohepatic circulation, acting like bile acid sequestrants.Conclusion. It was shown that administration of L-RAG together with ezetimibe or rosuvastatin led to a better decrease in the TC, TAG, LDL-C levels than with polysaccharide monotherapy or comparison drugs alone. The obtained data substantiate the prospects of using L-RAG in the complex therapy of hyperlipidemia.